2016
DOI: 10.1016/j.ecolecon.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Measuring nuclear power plant externalities using life satisfaction data: A spatial analysis for Switzerland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Differentiating their analysis by distance from the nearest nuclear plant, Goebel et al (2013) found that those results apply equally to individuals within a 50km radius from the nearest plant and individuals outside that radius. Welsch and Biermann (2016) found that the satisfaction-distance relationship in Switzerland changed significantly after the Fukushima disaster. In particular, life satisfaction of individuals whose nearest nuclear plant was at an intermediate distance (40-85 km) dropped, which the authors take to indicate that, due to an information shock provided by the spatial extent of the Fukushima event, individuals at places previously considered safe reassessed distance-dependent expectations of potential damage size.…”
Section: Valuation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiating their analysis by distance from the nearest nuclear plant, Goebel et al (2013) found that those results apply equally to individuals within a 50km radius from the nearest plant and individuals outside that radius. Welsch and Biermann (2016) found that the satisfaction-distance relationship in Switzerland changed significantly after the Fukushima disaster. In particular, life satisfaction of individuals whose nearest nuclear plant was at an intermediate distance (40-85 km) dropped, which the authors take to indicate that, due to an information shock provided by the spatial extent of the Fukushima event, individuals at places previously considered safe reassessed distance-dependent expectations of potential damage size.…”
Section: Valuation Studiesmentioning
confidence: 99%
“…The main result is that stated willingness to pay for increased insurance coverage against nuclear accidents decreases with distance from plant once attitudes influencing choice of residential location are controlled for. Welsch and Biermann (2016) applied the experienced preference method, also focusing on Switzerland. They investigated the relationship between Swiss citizens' life satisfaction and the distance of their place of residence from the nearest nuclear power plant and found a statistically and economically significant satisfaction-distance gradient.…”
Section: Valuation Studiesmentioning
confidence: 99%
“…Life satisfaction has also been used as a proxy for experienced utility in approaches that monetarize the impacts of natural hazards (e.g., Luechinger and Raschky 2009) with natural disasters causing a welfare loss (called the lifesatisfaction approach; see Welsch 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to Pearce (2001), an externality is a consequence (either positive or negative) generated by an economic activity and imposed on third parties where the impacts cannot be priced. Public perception of nuclear energy has been always influenced by the effects of externalities (Folland & Hough, 2000;OECD, 2003;Welsch & Biermann, 2016).…”
Section: Conceptualizing Externalitiesmentioning
confidence: 99%